»Splošna zgradba sveta« v Traktatu: Nekaj misli ob izidu novega prevoda Wittgensteinovega Traktata - Ule, Andrej (Analiza: časopis za kritično misel, 2025)
“The General Structure of the World” in Tractatus: Some Thoughts on The Release of the New Translation of Wittgenstein’s Tractatus I am debating the meaning of the so-called general structure of the world and the completely general (completely generalized) sentences in Wittgenstein’s Tractatus Logico -Philosophicus. I find that any comparison of completely general sentences and elementary sentences corresponds to something impossible, namely wanting to say something meaningful about the world as a limited (and structured) whole. Does this mean that all statements about facts and the world, especially about all facts and the whole world, must be stopped? I don’t think so, because to stop talking about something doesn’t necessarily mean that we’ve transcended that speech, it’s also necessary to transcend any need or desire for such speech. According to Wittgenstein, this requires much more than the rejection of meaningless sentences, namely, it also requires reference to the meaning of the world (6.41) through the “transcendental” unity of the world and life (5.621).